Aza-Anthraquinone derivative as a highly stable negolyte for acidic aqueous organic flow batteries - Li, Qiujun; Artault, Maxime; Maouche, Chanez; Gonzalez, Gabriel; Pihko, Petri M.; Peljo, Pekka (Elsevier, 2026)
Aqueous organic flow batteries (AOFBs) offer a scalable pathway for long-duration energy storage, yet their performance is often limited by the solubility, stability, or kinetic behavior of organic redox materials. We report a molecular design strategy based on the N-alkylation of 5,8-difluoro-2-aza-anthraquinone to access a new class of quaternized pyridinium salts (AAQ-1, AAQ-2, AAQ-3). N-alkylation of the pyridinium group enhanced solubility and enabled the tuning of redox behavior. AAQ-1 displayed superior electrochemical characteristics, including high solubility (847 mM in 2 M H₂SO₄) and fast charge transfer kinetics (k0 = 2.6 × 10−2 cm/s). Full-cell tests at both low and high concentrations further demonstrated very good stability, with a small capacity fade of 0.05% per day at high concentration, reaching a volumetric capacity of 25.6 Ah/L and a theoretical maximum of 43.4 Ah/L. AAQ-3 showed stable cycling at low concentration with small capacity decay of 0.46% per day. Post-mortem analyses on AAQ-1 revealed no structural degradation. Additionally, Pourbaix analysis confirmed a 2e−/2H+ proton-coupled electron transfer mechanism active under acidic conditions. This work introduces a practical, scalable, and tuneable redox platform for AOFBs. Through functional design, we demonstrate the feasibility of high-performance organic negolytes for long-duration, sustainable energy storage systems.